Isatin-tethered halogen-containing acylhydrazone derivatives as monoamine oxidase inhibitor with neuroprotective effect - Sunil Kumar; Jong Min Oh; Prabitha Prabhakaran; Abhimanyu Awasti; Hoon Kim; Bijo Mathew (Scientific Reports, 2024)
Abstract Sixteen isatin-based hydrazone derivatives (IS1–IS16) were synthesized and assessed for their ability to inhibit monoamine oxidases (MAOs). All the molecules showed improved inhibitory MAO-B activity compared to MAO-A. Compound IS7 most potently inhibited MAO-B with an IC50 value of 0.082 μM, followed by IS13 and IS6 (IC50 = 0.104 and 0.124 μM, respectively). Compound IS15 most potently inhibited MAO-A with an IC50 value of 1.852 μM, followed by IS3 (IC50 = 2.385 μM). Compound IS6 had the highest selectivity index (SI) value of 263.80, followed by IS7 and IS13 (233.85 and 212.57, respectively). In the kinetic study, the Ki values of IS6, IS7, and IS13 for MAO-B were 0.068 ± 0.022, 0.044 ± 0.002, and 0.061 ± 0.001 μM, respectively, and that of IS15 for MAO-A was 1.004 ± 0.171 μM, and the compounds were reversible-type inhibitors. The lead compounds were central nervous system (CNS) permeable, as per parallel artificial membrane permeability assay (PAMPA) test results. The lead compounds were examined for their cytotoxicity and potential neuroprotective benefits in hazardous lipopolysaccharide (LPS)-exposed SH-SY5Y neuroblastoma cells. Pre-treatment with lead compounds enhanced anti-oxidant levels (SOD, CAT, GSH, and GPx) and decreased ROS and pro-inflammatory cytokine (IL-6, TNF-alpha, and NF-kB) production in LPS-intoxicated SH-SY5Y cells. To confirm the promising effects of the compound, molecular docking, dynamics, and MM-GBSA binding energy were used to examine the molecular basis of the IS7-MAO-B interaction. Our findings indicate that lead compounds are potential therapeutic agents to treat neurological illnesses, such as Parkinson's disease.